Assessment of feasibility and utility of universal referral to specialty palliative care in a multidisciplinary amyotrophic lateral sclerosis clinic: A cohort study. Issue 6 (18th February 2021) - Hafer, Julia; Jensen, Sarah; Wiedau‐Pazos, Martina; Mehta, Ambereen K.
Abstract: Introduction: Although the value of palliative care integration in multidisciplinary amyotrophic lateral sclerosis (ALS) clinics has been increasingly recognized, limited data are available demonstrating the feasibility and utility of a palliative care specialist embedded in an ALS clinic. The purpose of this study is to describe the feasibility and utility of a universal outpatient referral model for specialty palliative care for patients with amyotrophic lateral sclerosis. Methods: This is a retrospective cohort study of initial patient visits with a palliative care physician in a multidisciplinary ALS clinic at an academic institution. All patients were referred to an embedded palliative care physician from January to December 2019. Results: Within the study period, 52 of 69 (75%) patients with a confirmed diagnosis of ALS were seen by the palliative care physician. The most common reason patients were not seen by palliative care was a lack of insurance authorization (n = 5). At the visit, 94% of patients discussed at least one advance care planning or goals of care topic. The most common advance care planning topic discussed was code status (40%). The most common goals of care topic discussed was meaning and values (57%). Symptom management was discussed with 40 patients (77%). The most common symptom addressed was pain and/or muscle spasms (33%). Discussion: These data support the feasibility and utility of universal, outpatient palliative care referral for patients with ALS. Further research is necessary to determine the long‐term effect on outcomes for this population. Abstract : See Editorial on pages 790–792 in this issue .